A model library for simulation and benchmarking of integrated urban wastewater systems. (July 2017) - Saagi, R.; Flores-Alsina, X.; Kroll, S.; Gernaey, K.V.; Jeppsson, U.
Abstract: This paper presents a freely distributed, open-source toolbox to predict the behaviour of urban wastewater systems (UWS). The proposed library is used to develop a system-wide Benchmark Simulation Model (BSM-UWS) for evaluating (local/global) control strategies in urban wastewater systems (UWS). The set of models describe the dynamics of flow rates and major pollutants (COD, TSS, N and P) within the catchment (CT), sewer network (SN), wastewater treatment plant (WWTP) and river water system (RW) for a hypothetical, though realistic, UWS. Evaluation criteria are developed to allow for direct assessment of the river water quality instead of the traditional emission based metrics (for sewer overflows and WWTP discharge). Three case studies are included to illustrate the applicability of the proposed toolbox and also demonstrate the potential benefits of implementing integrated control in the BSM-UWS platform. Simulation results show that the integrated control strategy developed to maximize the utilization of the WWTP's capacity represents a balanced choice in comparison to other options. It also improves the river water quality criteria for unionized ammonia and dissolved oxygen by 62% and 6%, respectively. Highlights: A freely distributed, open-source toolbox is developed to describe an urban wastewater system (UWS). The benchmark layout (BSM-UWS) is described. A set of criteria to evaluate sewer overflow, wastewater discharges and river water quality are proposed. Demonstrative control alternatives are evaluated to highlight the usefulness of the platform.